The Association of Serum Vitamin D Levels and Short Term and 6-month Outcomes among Patients with Acute Coronary Syndrome - Mohsen Asadi Qomi; Sepehr Gohari; Hassan Ahangar; Ahmad Jalilvand; Seyed Jamal Moosavi; Koorosh Kamali; Mohammad Masoud Vakili; Tara Reshadmanesh (Publisher: Shahid Beheshti University of Medical Sciences)
Introduction: vitamin D affects the function of most of the cells in the body, including myocytes and endothelial cells, and also affects platelet function. This study aims to evaluate the relation between vitamin D deficiency and in-hospital and 6-month outcomes of patients with the acute coronary syndrome.Methods: This was a prospective cohort study of patients admitted to Mousavi hospital with the diagnosis of acute coronary syndrome. A venous blood sample obtained from patients at the time of admission and 25-hydroxyvitamin D, lipid profile, and hs-troponin-I levels were measured. After coronary angiography, the severity of the coronary artery stenosis was calculated by the syntax score. Patients also evaluated in-hospital outcomes and even followed up for 6-month results.Results: Totally, 204 patients were included in the study. The mean ± SD of age was 60 ± 11.6-year-old. The overall vitamin D deficiency was 80.9%. There was no association between vitamin D deficiency and in-hospital and 6-month mortality in patients with acute coronary syndrome (P = 0.824). There was a direct and statistically significant association between vitamin D levels and HDL cholesterol (P = 0.011). Twenty-eight percent of patients with negative hs-troponin-I and 14% with positive hs-troponin-I had normal vitamin D levels, which was statistically significant (P = 0.045).Conclusion: This study does not demonstrate an association between vitamin D levels and in-hospital and 6-month outcomes in patients with the acute coronary syndrome.